Hubungan Dukungan Keluarga dengan Kecemasan Sosial Korban Perundungan Siber pada Remaja SMA di Kota Bandung - Farisha Febriana Supyan; Ihsana Sabriani Borualogo (Bandung Conference Series: Psychology Science, 2022)
Abstract. The research outcomes regarding the family support and social anxiety experienced by the victims of cyberbullying are still being debated. This study aims to determine the relationship of family support towards social anxiety of cyber bullying victims in high school students in Bandung City. The participants of this study (N = 221; 55.2% female and 44.8% male) were high school students aged 15-18 years old in Bandung City. The sampling technique used is convenience sampling. This study used linear regression analysis to examine the contribution of family support towards social anxiety. Family support was measured using the Child and Adolescent Social Support Scale (CASSS), the social anxiety variable was measured using the Social Anxiety Scale for Adolescent (SAS-A) and the cyberbullying variable used the Cyber ​​Bullying Victim. The results of this research show that the more often parents exhibit pride (β = .180; p < .05), understand the victim (β = -.242; p < .05), and inform the victim nicely if they make a mistake (β = -.248; p < .05), the less the fear of being evaluated negatively by others is felt by victim, and vice versa. Likewise, the more often parents praise the victim (β = .203; p < .05), the less social avoidance felt by the victim. Hence, the family support plays a significant roles in lessening social anxiety felt by the victims of cyberbullying. Abstrak. Hasil-hasil penelitian mengenai dukungan keluarga dan kecemasan sosial yang dirasakan oleh korban perundungan siber masih menjadi perdebatan. Penelitian ini bertujuan untuk mengetahui hubungan dukungan keluarga dengan kecemasan sosial korban perundungan siber pada remaja SMA di Kota Bandung. Partisipan penelitian ini (N = 221; 55.2% perempuan dan 44.8% laki-laki) adalah remaja SMA berusia 15-18 tahun di Kota Bandung. Teknik sampling yang digunakan adalah convenience sampling. Penelitian ini menggunakan analisis regresi linier untuk menguji kontribusi dukungan keluarga dengan kecemasan sosial. Dukungan keluarga diukur menggunakan alat ukur Child and Adolescent Social Support Scale (CASSS), variabel kecemasan sosial diukur menggunakan alat ukur Social Anxiety Scale for Adolescent (SAS-A) dan variabel perundungan siber diukur menggunakan alat ukur Korban Perundungan Siber. Hasil menunjukkan semakin sering orang tua menunjukkan rasa bangga (β = .180; p < .05), memahami korban (β = -.242; p < .05), dan memberi tahu secara baik-baik ketika korban melakukan kesalahan (β = -.248; p < .05) maka ketakutan di evaluasi negatif oleh orang lain yang dirasakan korban akan menurun, dan begitupun sebaliknya. Begitupun semakin sering orang tua memuji korban (β = .203; p < .05) maka penghindaran sosial yang dirasakan korban akan menurun. Sehingga dukungan keluarga berperan penting dalam menurunkan kecemasan sosial yang dirasakan oleh korban perundungan siber.